Simulasi Usaha sebagai Media Peningkatan Literasi Keuangan dan Kewirausahaan Siswa SMK Muhammadiyah 5 Jakarta - Vita Bintang Apriyanti; Farida Ismiyatun; Sri Mulwanti; Yoci Andeski (Jurnal PKM Manajemen Bisnis, 2026)
The high unemployment rate among vocational high school (Sekolah Menengah Kejuruan/SMK) graduates remains a significant challenge in Indonesia’s vocational education system. One of the main contributing factors is the dominance of a job-seeker mindset rather than a job-creator orientation. In addition, low practical financial literacy such as the inability to accurately calculate the Cost of Goods Sold (COGS) and the habit of mixing personal and business finances hinders students from developing independent entrepreneurial ventures. This Community Service Program (PMKM) aims to improve entrepreneurship understanding and financial management skills among 24 eleventh-grade accounting students at SMK Muhammadiyah 5 Jakarta. The implementation method uses an experiential learning approach through interactive workshops, financial engineering practice, and a Shock Market simulation designed to train students’ ability to make financial decisions under market pressure. The results show that business simulations using virtual capital effectively help students apply accounting theory into real business practice. Students demonstrated improved understanding of separating personal and business finances, the ability to systematically calculate COGS, and increased motivation toward entrepreneurship. Early entrepreneurship education is expected to shape vocational school graduates who are independent, disciplined, and competitive in the future.